The Effect of Adlerian Play Therapy on Working Memory of Female Students Seven to Twelve Years Old With Mild Intellectual Disability - Navida Johari; Hooshang Mirzai; Hojat Allah Haghgoo; Samane Hosseinzadeh (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective Intellectual disability is a common neurodevelopmental disorder. Working memory deficit can affect children. One of the effective methods in the field of learning is playing games and the application of play therapy techniques. In this method, children are allowed to practice useful social behaviors and experience new thoughts and feelings in a safe environment with supportive relationships. This study aimed to examine the effectiveness of Adlerian play therapy on the working memory of female students aged 7 to 12 years with mild intellectual disability. Materials & Methods Out of 60 female students aged 7 to 12 years with a diagnosis of mild intellectual disability in Fatemeh Zahra Special School in Qom, 28 students met the inclusion criteria. They were divided into the experimental and control groups by 1: 1 random allocation. The experimental group received the Adlerian therapy protocol for ten weeks in three 45-minute sessions (30 sessions) every week. The working memory of both groups was examined in three stages, including pre-test, post-test, and one month later, without receiving any intervention for follow-up, by the fourth version of the Wechsler Intelligence Scale for Children, Fourth Edition (WISC-IV). Data analysis was done by Shapiro-Wilk, Friedman, Mann-Whitney, and Bonferroni tests and generalized estimation equation by SPSS software v. 22 at the significance level of 5%. Results Most of the subjects in each group were aged 7 years (first grade) with six people (43%), whereas the lowest frequency was related to the age of 9 years (third grade) with two people (14%) per group. The mean and standard deviation of the working memory subtest in the experimental group increased from 6.28 3.66 in the pre-test to 10.4 86 in the post-test and increased to 12.64 5.25 in the follow-up stage. However, in the control group, the mean and standard deviation changed from 5.92 3.19 in the pre-test to 5.64 3.17 and 5.85 3.41 in the post-test and follow-up, respectively. In the experimental group, there was a significant difference in the mean score of working memory in all stages of measurement (p< 0.05). In the pre-test stage, there was no significant difference in the mean score of working memory in the experimental and control groups (p>0.05). In the post-test stage, because the P was very close to 0.05, we can ignore it and consider it significant. In the follow-up stage, there was a significant difference in the mean score of working memory in the experimental and control groups (P<0.05). Conclusion It seems that child-centered Adlerian play therapy has a persistent effect on the working memory of students with mild intellectual disabilities. Therefore, Adlerian play therapy can be used in educational planning to enhance the working memory of these students